A New State of Being: The Lived Experience of Parental Bereavement. (February 2017) - Denhup, Christine Yvonne
In spite of growing bereavement literature, the meaning of the lived experience of parental bereavement is not well understood. This article presents selected findings from a Heideggerian hermeneutic phenomenological study which aimed to describe the lived experience of bereaved parents who experienced the death of a child due to cancer. Conversational interviews were conducted with six parents who experienced the death of a young child due to cancer at least one year prior to participation. The nature of parental bereavement was revealed to be a new state of being into which parents enter immediately after the death of a child and which has no end point. Findings will equip health professionals and others who work with bereaved parents with a deeper understanding of the meaning of parental bereavement.